Experimental Work on Using Fully Wrapped Post-Tensioned Metal Straps Around Normal Reinforced Concrete Beams to Increase Flexural Strength of R.C Beams - Abdullah, Wrya; Omar, Avesta; Rafiq, Serwan Khwrshid (Sulaimani Journal for Engineering Sciences, 2021)
To increase the capacity load carrying of the beams, post tensioned metal straps are fully wrapped around the beams in their tensile zone in this study. In total four normal R.C beams with the depth of 160 mm, height of 240 mm and total length of 2100 mm are cast and tested under four-point load testing. The number of variables is kept to minimum of two which are the number and location of the straps. It is found that using post tensioned metal straps fully wrapped around the beams can increase the load-carrying capacity of the beams by 36% at least and 39% at a max. The main factor in influencing the rate is the location of the straps. A complete guide on using the material along with its application on the beams are explicitly described in the paper.
Keywords: Bending failure; Post Tension Metal Strap (PTMS); Steel Strap (SS); Bending test; Load Carrying Capacity